PENGARUH GAYA KEPEMIMPINAN DAN KOMITMEN ORGANISASI TERHADAP KINERJA KARYAWAN PADA PT. BANK ACEH SYARIAH CABANG BENER MERIAH DAN CABANG TAKENGON MELALUI BUDAYA ORGANISASI SEBAGAI VARIABEL MODERASI - Irfan, Irfan; Aiyub, Aiyub; Iis, Em Yusuf (Universitas Malikussaleh, 2020)
AbstractThe research conducted to examine the influence of leadership style and organizational commitment and organizational culture on the employee performance and to examine the moderation effect of organizational culture. The sample of this research was 120 permanent employees at PT. Bank Aceh Syariah Branch of Bener Meriah and Branch of Takengon. The tool of analysis was Path analysis with SEM (stuctural equation modeling) method by using Amos. The research result partially indicated that leadership style and organizational commitment influenced positively and significantly on organizational culture, performance and organizational culture appearancely mediated leadership style with performance and organizational culture appearancely mediated organizational commitment with performance. Keyword: Leadership Style, Organizational Commitment, Organizational Culture, and Employee Performance.